PERANCANGAN SISTEM KERJA ERGONOMIS UNTUK MENGURANGI TINGKAT KELELAHAN - Husein, Torik; Kholil, M.; Sarsono, Ari (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
Less ergonomic job conditions will generate more worker fatigue, caused stress created by parts of the body that are not comfortable. Thereby the existing work system should be improved by incorporating ergonomic principles. This work system will be improved by rearranging equipments and modifying facility layout. To improve arrangement of the facility layout a cartography of process flow is made. Data is also collected to support creating a more ergonomic design. Collected data includes a questionnaire to list complaints from employees, worker anthropometry data, and direct interviews. Due to analysis and observation it is recommended to repair several identified equipments such as working chair and jig (packaging). Current equipments are not fit to be used and have the potency to generate worker illness. Survey results also indicate that there are complaints of performance decrease in the arm, waist, calf, hand, and shoulder. Complaints of pain in the waist and arm reach 12.4 percent.